Method for rapidly preparing nano-column current collector based on copper mesh

Through the rapid preparation of nanocolumn current collector based on copper mesh, the existing three-dimensional structure current collector preparation methods are solved, and the preparation of current collector with high specific surface area is realized to inhibit the generation of lithium dendrites. Improves the battery's cycle performance and rate performance.

CN119481085APending Publication Date: 2025-02-18GUOKE ENERGY (CHUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411795513.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing three-dimensional structure current collector preparation methods have problems such as complex preparation steps, long preparation time and prone to failure of the three-dimensional structure.

Method used

The method of rapid preparation of nanocolumn current collectors based on copper mesh is adopted. The copper mesh is pretreated by hydrochloric acid solution, and then soaked in an aqueous solution containing ammonium persulfate and sodium hydroxide, followed by an electrical reduction reaction to prepare a rich three-dimensional columnar network. Structural copper/copper grid electrode.

Benefits of technology

This method can significantly increase the specific surface area of ​​the current collector, reduce local current density, inhibit the generation of lithium dendrites, stabilize the SEI film, and provide a huge storage volume for lithium deposition, solve the volume expansion problem, and improve the cycle performance and magnification of the battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481085A_ABST
    Figure CN119481085A_ABST
Patent Text Reader

Abstract

The invention discloses a method for rapidly preparing a nanorod current collector based on a copper net, and relates to the technical field of lithium batteries. The method for rapidly preparing the nanorod current collector based on the copper mesh comprises the following steps: cleaning the copper mesh with a hydrochloric acid solution, deionized water and ethanol to obtain a pretreated copper mesh; adding the pretreated copper mesh into an aqueous solution containing ammonium persulfate and sodium hydroxide, soaking for 3-8 minutes, taking out, cleaning and drying to obtain a copper hydroxide / copper mesh electrode; and taking the copper hydroxide / copper mesh electrode as a negative electrode, graphite as a positive electrode and sodium sulfate and boric acid as electrolytes, carrying out an electroreduction reaction, and cleaning and drying after the reaction is finished to obtain the copper / copper mesh electrode. According to the method for rapidly preparing the nano-column current collector based on the copper net, the preparation steps are simplified, the preparation time is shortened, and the current collector prepared by the method can effectively promote uniform deposition of Li < + >, inhibit generation of lithium dendrites and improve the battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium batteries, and in particular to a method for quickly preparing a nano-column current collector based on a copper mesh. Background Art

[0002] The rapid consumption of traditional fossil fuels and the demand for high-energy-density batteries in modern society have triggered in-depth research on energy storage materials with great potential. The advantages of lithium metal, ultra-high theoretical capacity, low redox potential and low density, make lithium metal batteries one of the most promising energy storage systems. The uncontrolled dendrite growth and volume change of lithium metal during the cycle process lead to short cycle life and safety issues of lithium metal batteries, which hinder the practical application of lithium metal batteries. As an important component in the battery and a carrier for carrying lithium, copper foil is often used as the negative electrode current collector because of its abundant reserves, good ductility and high conductivity. However, the uneven surface of copper foil easily causes charge tip aggregation at the protrusions to induce the formation and growth of lithium dendrites. The two-dimensional planar structure leads to infinite volume expansion of lithium, and the lithium-phobicity of copper itself also increases the lithium nucleation barrier. During the charge and discharge cycle of the battery, the generation of dendritic lithium is a problem that cannot be ignored. The formation of such dendrites not only reduces the capacity of the battery, but also may cause serious safety problems such as short circuit, posing a huge threat to the long-term stable operation of the battery.

[0003] In response to the above problems, researchers have been looking for effective solutions. In recent years, a novel strategy has attracted widespread attention, that is, using a current collector with a three-dimensional structure to inhibit the growth of dendrite lithium. The design concept of this structure is to alleviate the generation and volume expansion of dendrite lithium by increasing the surface area and structural stability of the current collector. Specifically, copper nanowires prepared by a water bath method demonstrate the advantages of this three-dimensional structure. The high specific surface area of ​​this structure can effectively reduce the current density, thereby inhibiting the growth of dendrite lithium to a certain extent. At the same time, this structure can also provide nucleation sites for the deposition of lithium ions, which helps to improve the charge and discharge efficiency of the battery. More importantly, the three-dimensional structure can also provide a buffer space for volume expansion and enhance the structural stability of the battery. However, although this method of inhibiting the growth of dendrite lithium using a three-dimensional structure has many advantages, its preparation process still faces some challenges. At present, the preparation steps of the three-dimensional structure are relatively complicated and require a long preparation time, which to a certain extent limits its application in actual production. Therefore, simplifying the preparation steps, shortening the preparation time, and maintaining the effectiveness of the three-dimensional structure will be an important direction for future research. Summary of the invention

[0004] The purpose of the present invention is to provide a method for quickly preparing a nanorod current collector based on a copper mesh to solve the following technical problems: The existing method for preparing a three-dimensional structured current collector has the problems of complicated preparation steps, long preparation time and easy failure of the three-dimensional structure.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for rapidly preparing a nanorod current collector based on a copper mesh comprises at least the following steps: Pre-treating the copper mesh with a hydrochloric acid solution, and then cleaning the copper mesh with deionized water and ethanol to obtain a pre-treated copper mesh; The pretreated copper mesh is added into an aqueous solution containing ammonium persulfate and sodium hydroxide, soaked for 3-8 minutes, taken out, washed with deionized water and anhydrous ethanol, and dried in a drying oven at 50-60° C. for 5-20 hours to obtain a copper hydroxide / copper mesh electrode; The copper hydroxide / copper mesh electrode is used as the negative electrode, graphite is used as the positive electrode, sodium sulfate and boric acid are used as electrolytes, and an electric reduction reaction is carried out. After the reaction is completed, the negative electrode is rinsed with deionized water and dried in a drying oven at 50-60° C. for 5-20 hours to obtain a copper / copper mesh electrode.

[0006] As a further solution of the present invention: the concentration of the ammonium persulfate is 0.25-0.4 mol / L, and the concentration of the sodium hydroxide is 3-5 mol / L.

[0007] As a further embodiment of the present invention, the mass ratio of the ammonium persulfate to the sodium hydroxide is 1:2-3.

[0008] As a further solution of the present invention: the concentration of the sodium sulfate is 0.15-0.3 mol / L, and the concentration of the boric acid is 0.4-0.6 mol / L.

[0009] As a further embodiment of the present invention: the mass ratio of the sodium sulfate to the boric acid is 1:1-1.5.

[0010] As a further solution of the present invention: the current density of the electroreduction is 30-60 mA cm -2 , the electroreduction time is 180-220s.

[0011] As a further solution of the present invention: the size of the copper mesh is (1-2)×(2-4) cm 2 .

[0012] As a further solution of the present invention: the concentration of the hydrochloric acid solution is 3 mol / L, and the pretreatment time is 5-20 min.

[0013] Beneficial effects of the present invention: The method for rapidly preparing a nanocolumn current collector based on a copper mesh provided in the present application forms a copper / copper mesh electrode by converting a two-dimensional current collector into a three-dimensional current collector and forming uniformly distributed nanocopper columns on a copper foil substrate. The nanocopper columns prepared on the copper mesh substrate in the present application have a vertically upward columnar structure and a rich three-dimensional columnar network structure, which can significantly increase the specific surface area. By increasing the specific surface area of ​​the electrode, the local current density can be effectively reduced, thereby inhibiting the generation of lithium dendrites, stabilizing the SEI film, and providing a huge accommodation volume for lithium deposition, which has a better effect in solving the volume expansion problem.

[0014] The present application provides a method for rapidly preparing a nanocolumn current collector based on a copper mesh. The method uses a wet chemical method to etch a columnar copper hydroxide on a copper foil, and then uses an electroreduction method to prepare a nanocopper column. Under the reduction potential conditions, divalent copper can be rapidly reduced to metallic copper and retain its rich three-dimensional network-like nanostructure. The present application also controls the reaction time of copper hydroxide to be 3-8 minutes, and the current density of electroreduction to be 30-60 mA cm -2 , and the time of electro-reduction is 180-220s to control the density of the obtained nano copper pillars, and to improve the cycle performance and rate performance to the greatest extent. In addition, the present application is based on a method for quickly preparing a nano pillar current collector based on a copper mesh. The preparation method is very simple and takes very little time. The nano pillar structure prepared by the electro-reduction method has better stability than the nano pillar structure grown by other methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a scanning electron microscope image of a copper hydroxide / copper mesh electrode prepared in one embodiment.

[0016] Figure 2 : is a scanning electron microscope image of the copper / copper mesh electrode prepared in one embodiment.

[0017] Figure 3 1 is an X-ray diffraction pattern of the copper hydroxide / copper mesh electrode prepared in one embodiment.

[0018] Figure 4 1 is an X-ray diffraction pattern of a copper / copper mesh electrode prepared in one embodiment. DETAILED DESCRIPTION

[0019] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Example 1 A method for rapidly preparing a nanorod current collector based on a copper mesh comprises the following steps: 1.5×3cm 2 The copper meshes of different sizes were pretreated with 3 mol / L hydrochloric acid solution for 10 min, and then washed with deionized water and ethanol to obtain the pretreated copper meshes; The pretreated copper mesh was immersed in a 30 mL aqueous solution containing 2.05 g of ammonium persulfate and 4.95 g of sodium hydroxide. After immersion for 5 min, the light blue copper mesh was taken out from the solution, washed five times with deionized water and anhydrous ethanol, and dried in a drying oven at 60 ° C for 10 h to obtain a copper hydroxide / copper mesh electrode; The copper hydroxide / copper mesh electrode obtained above was used as the negative electrode, the graphite rod was used as the positive electrode, and 30 ml of a solution containing 0.85 g of sodium sulfate and 0.93 g of boric acid was used as the electrolyte to carry out an electroreduction reaction. The constant current technique was used at a current density of 40 mA cm -2 The reaction was carried out for 200 seconds. After the reaction, the negative electrode was rinsed with deionized water five times and dried in a drying oven at 60°C for 10 hours to obtain a copper / copper mesh electrode.

[0021] Example 2 A method for rapidly preparing a nanorod current collector based on a copper mesh comprises the following steps: 1.5×3cm 2 The copper meshes of different sizes were pretreated with 3 mol / L hydrochloric acid solution for 10 min, and then washed with deionized water and ethanol to obtain the pretreated copper meshes; The pretreated copper mesh was immersed in a 30 mL aqueous solution containing 2.75 g of ammonium persulfate and 5.40 g of sodium hydroxide. After immersion for 5 min, the light blue copper mesh was taken out from the solution, washed five times with deionized water and anhydrous ethanol, and dried in a drying oven at 60 ° C for 10 h to obtain a copper hydroxide / copper mesh electrode. The copper hydroxide / copper mesh electrode obtained above was used as the negative electrode, the graphite rod was used as the positive electrode, and 30 ml of a solution containing 0.85 g of sodium sulfate and 0.93 g of boric acid was used as the electrolyte to carry out an electroreduction reaction. The constant current technique was used at a current density of 40 mA cm -2 The reaction was carried out for 200 seconds. After the reaction, the negative electrode was rinsed with deionized water five times and dried in a drying oven at 60°C for 10 hours to obtain a copper / copper mesh electrode.

[0022] Example 3 A method for rapidly preparing a nanorod current collector based on a copper mesh comprises the following steps: 1.5×3cm 2 The copper meshes of different sizes were pretreated with 3 mol / L hydrochloric acid solution for 10 min, and then washed with deionized water and ethanol to obtain the pretreated copper meshes; The pretreated copper mesh was immersed in a 30 mL aqueous solution containing 2.05 g of ammonium persulfate and 4.95 g of sodium hydroxide. After immersion for 5 min, the light blue copper mesh was taken out from the solution, washed five times with deionized water and anhydrous ethanol, and dried in a drying oven at 60 ° C for 10 h to obtain a copper hydroxide / copper mesh electrode; The copper hydroxide / copper mesh electrode obtained above was used as the negative electrode, the graphite rod was used as the positive electrode, and 30 ml of a solution containing 1.25 g of sodium sulfate and 1.10 g of boric acid was used as the electrolyte to carry out an electroreduction reaction. The constant current technique was used at a current density of 40 mA cm -2 The reaction was carried out for 200 seconds. After the reaction, the negative electrode was rinsed with deionized water five times and dried in a drying oven at 60°C for 10 hours to obtain a copper / copper mesh electrode.

[0023] Comparative Example 1 A method for rapidly preparing a nanorod current collector based on a copper mesh comprises the following steps: 1.5×3cm 2 The copper meshes of different sizes were pretreated with 3 mol / L hydrochloric acid solution for 10 min, and then washed with deionized water and ethanol to obtain the pretreated copper meshes; The pretreated copper mesh was immersed in 60 mL of an aqueous solution containing 4.10 g of ammonium persulfate and 9.90 g of sodium hydroxide. After immersion for 20 min, the light blue copper mesh was taken out from the solution, washed five times with deionized water and anhydrous ethanol, and dried in a drying oven at 60 ° C for 10 h to obtain a copper hydroxide / copper mesh electrode. The copper hydroxide / copper mesh electrode obtained above was used as the negative electrode, the graphite rod was used as the positive electrode, and 30 ml of a solution containing 1.70 g of sodium sulfate and 1.86 g of boric acid was used as the electrolyte to carry out an electroreduction reaction. The constant current technique was used at a current density of 40 mA cm -2 The reaction was carried out for 400 s. After the reaction, the negative electrode was rinsed with deionized water five times and dried in a drying oven at 60°C for 10 h to obtain a copper / copper mesh electrode.

[0024] Comparative Example 2 The preparation method of biomass-derived copper nanowire copper current collector comprises the following steps: Add 250-4500ml of deionized water and 2-36ml of 1mg / ml bacterial cellulose dispersion into a 500-5000ml beaker. Stir with a magnetic stirrer (200 rpm) during the reaction. Add 50-900mg of polyvinyl pyrrolidone (PVP). After 5min, add 0.1-1.8g of copper chloride dihydrate (CuCl 2 ·2H 2O), and then add 5-90ml hydrazine hydrate solution after 20min, react for 30min, pour the solution containing copper nanowires into a 600-mesh stainless steel filter screen, filter and wash it repeatedly with ethanol several times, then disperse it in a small amount of ethanol again, place it in a 500ml polytetrafluoroethylene reactor lining, dry it in an oven at 60℃, and then place it in a tubular furnace under hydrogen and argon atmosphere at 200-400℃ for annealing for 2-8h (5℃ / min heating and cooling speed) to obtain copper nanowires; Add 250-4500 ml of deionized water into a 500-5000 ml beaker, take 100-500 mg of the prepared copper nanowires into the beaker, and stir magnetically (speed 200 rpm). After the copper wires are evenly dispersed, filter to form a film, transfer to an oven for drying, and reduce at a high temperature of 800-1000 ° C in a hydrogen and argon atmosphere for 2-4 h (heating rate 10 ° C / min) to obtain a copper current collector material.

[0025] Comparative Example 3 1.5×3cm 2 The copper meshes of different sizes were pretreated with 3 mol / L hydrochloric acid solution for 10 min, and then washed with deionized water and ethanol to obtain the pretreated copper mesh, which was a flat copper foil and used as a blank electrode.

[0026] Performance Testing X-ray diffraction analysis The copper hydroxide / copper mesh electrode and copper / copper mesh electrode prepared in Example 1 were cut into discs with a diameter of 12 mm by a slicer and placed directly in a glass sample slot. The crystal structure of the sample was analyzed by X-ray diffraction using a D8 ADVANCE X-ray diffractometer (Cu-Kα target, λ=0.15406 nm, scanning speed of 8° / min, 2θ angle range of 20°-80°). The XRD data were analyzed by Rietveld method using Maud software to obtain the phase composition and lattice structure parameters of the sample.

[0027] Field Emission Scanning Electron Microscope The copper hydroxide / copper mesh electrode and the copper / copper mesh electrode prepared in Example 1 were cut in the middle with a knife, and the cross-section / surface morphology and element distribution of the samples were analyzed using a Gemini SEM 300 scanning electron microscope and an energy dispersive spectrometer (EDS) to obtain the morphological changes and element distribution of the samples before and after modification, as well as the morphological changes of the samples before and after charge and discharge cycles and the morphological changes of surface deposited lithium.

[0028] Battery assembly and testing In order to test the electrochemical properties and battery performance of the prepared modified current collector, the present application assembled and tested Li-Cu half-cells. The batteries assembled in the present application all used CR2032 button cell accessories and Celgard2500 PP separators.

[0029] Li-Cu half-cell: The current collector prepared in Examples 1-3 and Comparative Examples 1-3 was used as the working electrode, the lithium metal sheet was used as the counter electrode, and the electrolyte was 1M LiFSI in DME lithium sulfur electrolyte. A CR2032 button half-cell was assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, diaphragm, and current collector to test its coulombic efficiency and cycle stability. The entire battery assembly process was carried out under H 2 O, O 2 The content was less than 1 ppm in the glove box.

[0030] Constant current charge and discharge test (GCD) This application uses the galvanostatic charge and discharge method to test the electrochemical performance of the electrode and the battery performance. The test is performed by energizing the tested battery with a certain current, recording the parameters such as the battery charge / discharge capacity, voltage, test time and number of cycles under test, and analyzing the collected battery charge and discharge curves to obtain the electrochemical performance and battery performance of the corresponding battery system such as coulomb efficiency, voltage polarization, and cycle life; the test results are shown in the table below; Electrochemical Impedance Spectroscopy (EIS) Electrochemical impedance spectroscopy is used to measure the impedance of the electrode. The test applies a small-amplitude multi-frequency AC signal to the test battery, measures and records the corresponding change relationship between the phase angle and impedance of the test battery, and calculates various parameters in the electrode process dynamics through the analysis of each basic element in the equivalent circuit diagram, including interface charge transfer impedance, SEI membrane impedance, and parameters in the diffusion mass transfer process. This application uses a CHI660E electrochemical workstation to perform electrochemical impedance spectroscopy testing on the battery within a frequency range of 105-0.1Hz, with the initial voltage set to the battery open circuit voltage and the amplitude set to 5mV; the test results are shown in the table below; Cyclic voltammetry (CV) The cyclic voltammetry curve of the sample is measured and collected through the electrochemical cyclic voltammetry test. This test controls the potential of the electrode, uses a continuous triangular wave signal as the potential control signal, and performs multiple cyclic scans at a certain rate within the set potential range. The system records the curve of the current value of the test electrode changing with the electrode potential, analyzes the redox reaction occurring at each voltage stage, and can also evaluate the reversibility of the electrode electrochemical reaction. This experiment uses the Chenhua CHI660E electrochemical workstation to perform cyclic voltammetry tests on the modified electrode; the test results are shown in the table below;

[0031] Please refer to Figure 1-Figure 4 , Figure 1 is a scanning electron microscope image of the copper hydroxide / copper mesh electrode obtained in the preparation process of Example 1, Figure 2 is a scanning electron microscope image of the copper / copper mesh electrode prepared in Example 1, Figure 3 is the X-ray diffraction pattern of the copper hydroxide / copper mesh electrode obtained in the preparation process of Example 1, Figure 4 is the X-ray diffraction pattern of the copper / copper mesh electrode prepared in Example 1. Figure 1 and Figure 3 It can be seen that the scanning electron microscope image shows that the present application uniformly etches a large number of columnar structures on the copper mesh substrate, and the XRD results confirm that the multiple diffraction peaks of the electrode sample in the range of 20°-80° belong to copper hydroxide (PDF#13-0420), indicating that the columnar structure sample synthesized on the copper mesh substrate is columnar copper hydroxide. Figure 3 and Figure 4 It can be seen that the scanning electron microscope image shows that after electro-reduction, the columnar copper hydroxide etched by wet chemical method forms a nano-column structure after the electro-reduction reaction. The XRD results confirm that the electrode sample only has a strong diffraction peak signal of metal Cu (PDF#04-0836) in the range of 20°-80°, indicating that the present application reduces the columnar copper hydroxide into copper nano-columns by electro-reduction, and the obtained copper nano-columns are evenly distributed on the copper foil substrate.

[0032] As can be seen from the above table, Examples 1-3 are current collectors prepared by the method of rapidly preparing nanocolumn current collectors based on copper mesh in this application. The battery obtained by using the prepared current collector as a working electrode has good electrical properties, and the electrode can be stably cycled 280 times, with an average coulombic efficiency of 99.0%, a maximum specific capacity of more than 175 mAh / g, and a capacity retention rate of more than 88%. In Comparative Example 1, the reaction time of copper hydroxide was increased, and the electrochemical performance of the obtained electrode deteriorated, indicating that the excessive density of copper hydroxide nanocolumns will hinder the transmission of lithium ions, resulting in a decrease in the deposition / stripping stability of the three-dimensional current collector, making it difficult to perform long-term stable cycles. Comparative Example 2 is a copper current collector prepared by biomass-derived copper nanowires, and the obtained electrode cycle stability is reduced, indicating that the structure of the nanocolumn structure obtained by the preparation method provided in this application is more stable. Comparative Example 3 is a blank aluminum foil with a two-dimensional structure, and the electrical properties of the electrode are poor in all aspects, indicating that the copper nanocolumn structure after electrochemical reduction in this application has higher cycle stability than the blank copper foil, and is more conducive to the reversible deposition / stripping of lithium.

[0033] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for rapidly preparing a nanorod current collector based on a copper mesh, characterized in that: At least the following steps are included: Pre-treating the copper mesh with a hydrochloric acid solution, and then cleaning the copper mesh with deionized water and ethanol to obtain a pre-treated copper mesh; The pretreated copper mesh is added into an aqueous solution containing ammonium persulfate and sodium hydroxide, soaked for 3-8 minutes, taken out, washed with deionized water and anhydrous ethanol, and dried in a drying oven at 50-60° C. for 5-20 hours to obtain a copper hydroxide / copper mesh electrode; The copper hydroxide / copper mesh electrode is used as the negative electrode, graphite is used as the positive electrode, sodium sulfate and boric acid are used as electrolytes, and an electric reduction reaction is carried out. After the reaction is completed, the negative electrode is rinsed with deionized water and dried in a drying oven at 50-60° C. for 5-20 hours to obtain a copper / copper mesh electrode.

2. The method for rapidly preparing a nanorod current collector based on a copper mesh according to claim 1, characterized in that: The concentration of the ammonium persulfate is 0.25-0.4 mol / L, and the concentration of the sodium hydroxide is 3-5 mol / L.

3. The method for rapidly preparing a nanorod current collector based on a copper mesh according to claim 2, characterized in that: The mass ratio of the ammonium persulfate to the sodium hydroxide is 1:2-3.

4. The method for rapidly preparing a nanorod current collector based on a copper mesh according to claim 1, characterized in that: The concentration of the sodium sulfate is 0.15-0.3 mol / L, and the concentration of the boric acid is 0.4-0.6 mol / L.

5. The method for rapidly preparing a nanorod current collector based on a copper mesh according to claim 4, characterized in that: The mass ratio of the sodium sulfate to the boric acid is 1:1-1.

5.

6. The method for rapidly preparing a nanorod current collector based on a copper mesh according to claim 1, characterized in that: The current density of the electroreduction is 30-60 mA cm -2 , the electroreduction time is 180-220s.

7. The method for rapidly preparing a nanorod current collector based on a copper mesh according to claim 1, characterized in that: The size of the copper mesh is (1-2) × (2-4) cm 2 .

8. The method for rapidly preparing a nanorod current collector based on a copper mesh according to claim 1, characterized in that: The concentration of the hydrochloric acid solution is 3 mol / L, and the pretreatment time is 5-20 min.